English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

9x^2 - 24x = -13
Can someone show the steps involved in solving this I'm having major problems.

2006-11-21 15:47:06 · 6 answers · asked by vette_311 2 in Science & Mathematics Mathematics

6 answers

Quadratic Formula solution

9x² - 24x = - 13

9x² - 24x + 13 = - 3 + 13

9x² - 24x + 13

- - - - - - - - - - -

a = 9
b = - 24
c = 13

- - - - - - - - -

x = - b ± √b² - 4ac/2a

x = - 24 ± √(- 24)² - 4(9)(13) / 2(9)

x = - 24 ± √576 - 468 / 18

x = - 24 ± √108 / 18

x = - 24 ± 10.39230485 / 18

- - - - - - - - - - - - - - -

solvint for -

x = - 24 - 10.39230486 / 18

x = - 34.39230485 / 18

x = 1.910683603

- - - - - - - - - - - -

solving for +

x = - 24 + 10.39230485 / 18

x = - 13.60769515 / 18

x = - 0.755983064

- - - - - - -s-

2006-11-21 22:53:42 · answer #1 · answered by SAMUEL D 7 · 1 0

Thedeath used a faulty method and got totally wrong answers------

Add 13 to both sides---> 9x^2-24x+13 = 0
The quadratic formula gives:

x = (24 +- sqrt(24^2 - 4*9*13))/(2*9) = 1.9107, and 0.75598

I checked these answers; they are CORRECT

2006-11-21 16:03:06 · answer #2 · answered by Steve 7 · 3 0

Set the equation to zero:
9x^2-24x+13=0

Use the quadratic formula:
x=-b±√b^2-4ac/2a
a=9,b=-24,c=13

All you do is plug in the numbers and solve it.

2006-11-21 16:18:44 · answer #3 · answered by Anonymous · 2 0

to solve this bring add both sides by 13 to make the RS =0
Then you get 9x^2-24x+13=0
multiply the first and last term together and you get 117
find two number that add to get -24 and multiply to get 117 since there is no *whole number* that add to get -24 and multiply to get 117 you basically use the quadratic formula
-b+or-square root (b^2-4ac)/2a a=9 b=-24 c=13
when you do all this
i am so lazily to write it out you will get x=1.910683603 or x=0.755983064

2006-11-21 15:58:58 · answer #4 · answered by ayok 2 · 4 0

9x^2-24x+13=0
(3x+8)(3x-3)=0
so either
3x+8 = 0 or 3x-3=0
so
x=-8/3 or x = 1

2006-11-21 15:57:01 · answer #5 · answered by Heather M 2 · 1 4

3x(x-8) = -13

3x = -13 ; x-8 = -13
x=-13/3 x=-13+8

2006-11-21 15:52:58 · answer #6 · answered by Anonymous · 2 2

fedest.com, questions and answers